Everyday Life for First-Time Fathers During Pregnancy and After the Baby is Born - Lepistö, Sari; Koivisto, Anna-Maija; Alasuvanto, Elina; Piironen, Tiia; Kylmä, Jari; Paavilainen, Eija; Kanzaki, Mitsuko (European Journal of Applied Sciences, 2025)
Becoming a father is one of the most significant events in a man’s life, bringing with major changes, emotions and challenges. The birth of a new family member affects fathers’ everyday lives, for example through the functioning of the family, their mood and the feeling of parenthood. The concept of fatherhood has modernized towards a more diverse and involved fatherhood instead of a narrow-minded concept. Despite this, the role of fathers as equal parents is not yet recognized well enough in the healthcare system. The aim of this research was to describe the experiences of first-time fathers during pregnancy and the first eight months of their baby’s life. The study is part of an international longitudinal study in Finland and Japan. The survey used the Japanese version of Family Function Scale (FFS) and Sense of Parenting Burden Scale (Burden). The data were analyzed by statistical methods. Fathers assess family functioning as fairly good during pregnancy and after the birth of the baby. Fathers assess the sense of parenting burden increasing in a statistically significant during the first eight months of the baby’s life. The background variables had no statistically significant associations with family functioning or experience of parenting burden. Although fathers assess family functioning, and their experience of the burden for good, they need support in parenting and fatherhood.